2016 IEEE International Symposium on Information Theory (ISIT) 2016
DOI: 10.1109/isit.2016.7541276
|View full text |Cite
|
Sign up to set email alerts
|

On caching with more users than files

Abstract: Caching appears to be an efficient way to reduce peak hour network traffic congestion by storing some content at the user's cache without knowledge of later demands. Recently, Maddah-Ali and Niesen proposed a two-phase, placement and delivery phase, coded caching strategy for centralized systems (where coordination among users is possible in the placement phase), and for decentralized systems. This paper investigates the same setup under the further assumption that the number of users is larger than the number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 17 publications
(68 reference statements)
0
67
0
Order By: Relevance
“…However in the case of uniform file popularity, the achievable rates provided in these works reduce to the results of [10] or [17], while our proposal strictly improves the state of the arts in both [10] and [17] by developing a novel delivery strategy that exploits the commonality of the user demands. There have also been several proposed schemes that aim to minimize the peak rates [12], [16]. The main novelty of our work compared to their results is that we not only propose an optimal design that strictly improves upon all these works through a leader based strategy, but also provide an intuitive proof for its decodability.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…However in the case of uniform file popularity, the achievable rates provided in these works reduce to the results of [10] or [17], while our proposal strictly improves the state of the arts in both [10] and [17] by developing a novel delivery strategy that exploits the commonality of the user demands. There have also been several proposed schemes that aim to minimize the peak rates [12], [16]. The main novelty of our work compared to their results is that we not only propose an optimal design that strictly improves upon all these works through a leader based strategy, but also provide an intuitive proof for its decodability.…”
Section: Resultsmentioning
confidence: 91%
“…The problem of caching with uncoded prefetching was initiated in [12], [51], which showed that the scheme in [10] is optimal when considering peak rate and centralized caching, if there are more files than users. Although not stated in [12], [51], the converse bound in our paper for the special case of peak rate and centralized setting could have also been derived using their approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If A < 0, let s = = 1, we have (N, 0) ∈ S Lower from (15). Hence A + BN ≤ 0, and for any M ∈ [0, N ] we have…”
Section: Proof Of Theorem 1 and Theoremmentioning
confidence: 99%
“…5 Recall that in Section I-B we defined the XOR operation⊕ over the binary representations of the two messages of same length.…”
Section: Generalized Coded-cachingmentioning
confidence: 99%